The Analysis Study of Adenotonsillectomy for Obstructive Sleep Apnea and Quality of Life: A Systematic Review - Maura Widyaratri, Putri; Hermawan, Kevin Krishnadi; Satyarini, Nidyasari Citraningrum (Jurnal Health Sains, 2024)
The recommended therapy for children with obstructive sleep apnea syndrome (OSAS) is adenotonsillectomy. This review aims to eval__uate if adenoidectomy alone could be a viable treatment for children with OSAS, potentially reducing morbidity, mortality, and costs. The systematic review adheres to PRISMA 2020 guidelines to ensure current and comprehensive research. Publications from 2014 to 2024 were sourced from online databases, including PubMed, ScienceDirect, and SagePub, excluding reviews, previously published, and incomplete works. The search yielded 1,446 articles on PubMed, 2,514 on ScienceDirect, and 749 on SagePub. For the year 2014, the search found 913 articles on PubMed, 1,321 on ScienceDirect, and 749 on SagePub. Ultimately, eight studies met the inclusion criteria: five from PubMed, two from ScienceDirect, and one from SagePub. The review concludes that adenotonsillectomy in OSAS patients improves behavior, symptoms, and quality of life.